200 jaar UGent in 200 objecten : [kalender] van Dies Natalis tot Stichtingsdag : vrijdag 24 maart - maandag 9 oktober 2017 - De Rynck, Patrick; Dekeyser, Ann-Sofie; Goyvaerts, Agnes; Gunst, Petra; Mantels, Ruben; Verbeken, Pascal; Deceuninck, Benn; Burez, Michel; Devriendt, Mirjam; Hendryckx, Michiel; Provoost, Dominique; Roels, Geert (Veurne: Hannibal, 2017)
"Tekst: Patrick De Rynck, Ann-Sofie Dekeyser, Agnes Goyvaerts, Petra Gunst, Ruben Mantels, Pascal Verbeken ; Fotografie: Benn Deceuninck, Michel Burez, Mirjam Devriendt, Michiel Hendryckx, Dominique Provoost, Geert Roels"